Peluang Penerapan Produksi Bersih di Industri "Konveksi Kaos & Kemeja" Kota Pontianak - Nugraha, Adhitama Satya; Zaki Alqadrie, Syarif Muhammad (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
Various kinds of industrial activities besides having a positive impact also have a negative impact including non-product output which can be a polluter that harms the environment if it is not managed properly. Industrial waste is one of the serious problems in the era of industrialization. One of the industries that produce waste is the convection industry, which can have an impact on the environment if left untreated. Therefore, it must be handled from the beginning during the production process, one of the treatments is by applying clean technology. This research was conducted to identify the generation of waste generated in the clothing production process and to develop alternative clean production opportunities that can be applied along with an overview of economic and environmental benefits. Opportunities for the application of clean production that can be done is to recycle the fabric remnants from the production of T-shirt Shirt Convection into a variety of accessories that are worth selling with 4 different types of sewing patterns, namely abstraction, template, overlapping, and geometric patterns.